Study of River Pollution's Effect on Water Quality - Dr. Gargi (International Journal of Engineering and Management Research, 2019)
In order to control weeds, pests, and diseases in crops as well as for human and animal health, pesticides are a type of chemical that is used all over the world as herbicides, insecticides, fungicides, rodenticides, molluscicides, nematicides, and plant growth regulators. Application of pesticides results in increased crop and food productivity and a significant decrease in diseases carried by vectors. However, the environment in general, as well as the health of people, birds, and other animals in particular, has been seriously concerned by their uncontrolled and indiscriminate applications. The use of some of the least biodegradable and most environmentally persistent pesticides, such as organochlorines, is constantly increasing, despite many countries banning their use. Because of their quick lipid solubility and bioaccumulation in organisms other than their intended targets, pesticides pose serious health risks to living systems. Pesticides may have a number of unfavourable effects, even at low concentrations, which could be observed through biochemical, molecular, or behavioural means. Drainage, rainfall, microbial activity, soil temperature, treatment surface, application rate, solubility, mobility, and half-life of pesticides are some of the variables affecting pesticide and residue water pollution. More than 70% of the pesticides currently used in India are organochlorine insecticides like DDT and HCH. Reports from Delhi, Bhopal, and other cities, as well as some rural areas, have revealed the presence of pesticides at significant levels in fresh water systems and samples of bottled mineral water. This review has covered the effects of pesticide pollution on India's drinking water and riverine systems.